Towards a scaling-up of training and education for health workers - Isabel CF da Cruz (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2007)
The World Health Report 2006, Working together for health, recognized the centrality of the health workforce for the effective operation of country health systems and outlined proposals to tackle a global shortage of 4.3 million health workers. There is increasing evidence that that this shortage is interfering with efforts to achieve international development goals, including those contained in the Millenium Declaration and those of WHO's priority programmes.